A Review of Database Management Systems Suitable for Neuroimaging - Diallo, B.; Travere, J.-M.; Mazoyer, B. (Methods of Information in Medicine, 1999)
This study comprises a technical assessment of Database Management Systems (DBMS), which may be of use in the analysis of data obtained from human brain mapping procedures. Due to the large expansion of the neuroimaging field, the use of specialized database software to store and process neuroimages and their attached components is inevitable. The advent of multiple software products, a wealth of technical terms and a wide variety of other applications make the choice of a suitable program sometimes difficult. Through the inclusion of some basic and pertinent criteria (e.g., performance, ease of opening, standardization and portability), we present a descriptive comparison of 12 DBMSs currently available in the commercial and public domain. We have compared and tested three main architecture models which are currently available and assessed their potential applications for imaging purposes: relational, object-oriented, and hybrid. The findings of our study demonstrated that the Illustra™ software was the best suited for a neuroimaging environment because of its intrinsic ability to handle complex and large objects, such as 3D volumes or geometric structures.
Keywords: Databases; DBMS; Neuroimaging